2016
DOI: 10.1161/jaha.116.003433
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Lowers Blood Pressure by Improvement of Endothelial Dysfunction via AMPK‐Akt‐eNOS‐NO Pathway in the Spontaneously Hypertensive Rat

Abstract: BackgroundExercise is a major nonpharmacological treatment for hypertension, but its underlying mechanisms are still not completely elucidated. Irisin, a polypeptide containing 112 amino acids, which is secreted mainly by skeletal muscle cells during exercise, exerts a protective role in metabolic diseases, such as diabetes mellitus and obesity. Because of the close relationship between irisin and metabolic diseases, we hypothesized that irisin may play a role in the regulation of blood pressure.Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 70 publications
6
73
0
1
Order By: Relevance
“…This finding is consistent with our previous study which demonstrated that AMPK acted as a physiological suppressor of ER stress by maintaining SERCA activity and intracellular Ca 2+ homeostasis in endothelial cells (Dong et al , ). In addition, AMPK activation by irisin, a polypeptide containing 112 amino acids, secreted mainly by skeletal muscle cells during exercise, has been shown to lower BP in spontaneously hypertensive rats by improving NO bioactivity and endothelial cell function (Fu et al , ). This has been mechanistically attributed to the higher NO release by enhancing the phosphorylation and activation of endothelial NOS (eNOS) at Ser 1177 and Ser 633 (Chen et al , ; Zhang et al , ) and by blocking NO inactivation by reactive oxygen species (Deng et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our previous study which demonstrated that AMPK acted as a physiological suppressor of ER stress by maintaining SERCA activity and intracellular Ca 2+ homeostasis in endothelial cells (Dong et al , ). In addition, AMPK activation by irisin, a polypeptide containing 112 amino acids, secreted mainly by skeletal muscle cells during exercise, has been shown to lower BP in spontaneously hypertensive rats by improving NO bioactivity and endothelial cell function (Fu et al , ). This has been mechanistically attributed to the higher NO release by enhancing the phosphorylation and activation of endothelial NOS (eNOS) at Ser 1177 and Ser 633 (Chen et al , ; Zhang et al , ) and by blocking NO inactivation by reactive oxygen species (Deng et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium secretes various vasoconstrictors and vasodilators. The imbalance between the vasodilator NO and vasoconstrictor endothelin-1 in the endothelium contributes to endothelial dysfunction and increased peripheral vascular resistance and, subsequently, to hypertension [28-30]. …”
Section: Discussionmentioning
confidence: 99%
“…A higher level of NO improved endothelial function. 17 Another study focused on correlations between irisin and AH in pregnant and preeclamptic women. The researchers used ELISA kits to analyze the level of irisin in the blood.…”
Section: Adropin Irisin and Hypertensionmentioning
confidence: 99%